Nanoscale opening fabrication on Si (111) surface from SiO2 barrier for vertical growth of III-V nanowire arrays. (3rd July 2015) - Shi, Tuanwei; Wang, Xiaoye; Wang, Baojun; Wang, Wei; Yang, Xiaoguang; Yang, Wenyuan; Chen, Qing; Xu, Hongqi; Xu, Shengyong; Yang, Tao
Abstract We reported here a selectively additive process to fabricate nanoscale openings of an Si (111) surface from an SiO2 barrier layer. Such nanoscale openings are made for the growth of vertical III–V nanowires. The Si (111) surface protected by a patterned SiNx layer was thermally oxidized, which resulted in a selectively added SiO2 barrier layer. After removing the SiNx, nanoscale openings of the Si (111) surface were exposed for the nanowire growth. Arrays with patterned nanoholes of varied diameters from 60 nm to 334 nm have been used for position-controlled catalyst-free growth of vertical InAs nanowire arrays by metal-organic chemical vapor deposition. Correlations between the nanohole diameter and the diameter, length and growth yield of as-fabricated nanowire arrays have been investigated, showing a repeatable stability. This technique offers an alternative approach for the fabrication of novel III–V nanowire devices using vertical array configuration. A lateral thermal oxidation effect led to a smaller size of the Si opening than that of the SiNx protection nanoislands; therefore, the technique also offers a controllable way to produce nanoholes with an ultra-small diameter.